Content of web-based continuing medical education about HPV vaccination. Issue 35 (16th August 2017) - Kornides, Melanie L.; Garrell, Jacob M.; Gilkey, Melissa B.
Highlights: HPV epidemiology, vaccination coverage, administration, and safety were common in online CME. Strategies to increase vaccination and address parent concerns were less common. Future CME should focus on pragmatic approaches to improving vaccine delivery. Abstract: Background: Addressing low HPV vaccination coverage will require U.S. health care providers to improve their recommendation practices and vaccine delivery systems. Because readily available continuing medical education (CME) could be an important tool for supporting providers in this process, we sought to assess the content of web-based CME activities related to HPV vaccination. Methods: We conducted a content analysis of web-based CME activities about HPV vaccination available to U.S. primary care providers in May-September 2016. Using search engines, educational clearinghouses, and our professional networks, we identified 15 activities eligible for study inclusion. Through a process of open coding, we identified 45 commonly occurring messages in the CME activities, which we organized into five topic areas: delivering recommendations for HPV vaccination, addressing common parent concerns, implementing office-based strategies to increase HPV vaccination coverage, HPV epidemiology, and guidelines for HPV vaccine administration and safety. Using a standardized abstraction form, two coders then independently assessed which of the 45 messages each CME activity included. Results: CME activities varied in the amount of content they delivered, with inclusion of the 45 messages ranging from 17% to 86%. Across activities, the most commonly included messages were related to guidelines for HPV vaccine administration and safety. For example, all activities (100%) specified that routine administration is recommended for ages 11 and 12. Most activities (73%) also noted that provider recommendations are highly influential. Fewer activities modeled examples of effective recommendations (47%), gave specific approaches to addressing common parent concerns (47%), or included guidance on office-based strategies to increase coverage (40%). Conclusions: Given that many existing CME activities lack substantive content on how to change provider practice, future activities should focus on the practical application of interpersonal and organizational approaches for improving HPV vaccine delivery in the clinical setting.